Metabolic Syndrome and the Immunological Affair with the Blood–Brain Barrier - Mauro, Claudio; De Rosa, Veronica; Marelli-Berg, Federica; Solito, Egle (Frontiers in Immunology, 2015)
Epidemiological studies reveal an increased incidence of obesity worldwide, which is associated with increased prevalence and severity of cognitive disorders. The blood brain barrier represents the interface between the peripheral circulation and the brain, and plays a fundamental role in the cross-talk between these two compartments. The homeostatic function of the blood-brain barrier is the protection of the brain from peripheral insult/inflammation. Alterations in the function of the blood-brain barrier lead to pathologies of the central nervous system. Recently, metabolic imbalance has been shown to be an important risk factor associated with the decline of blood-brain barrier integrity and function. This has direct etiological consequences to a variety of cerebrovascular and neurodegenerative pathologies with great impact to society. Priority areas for future preclinical research include strategies to improve clinicians’ ability to diagnose, prevent, and manage blood-brain barrier abnormalities. In sharp contrast with epidemiological studies and clinical needs, little is known about the mechanisms that link metabolic syndrome to blood-brain barrier functionality and cognitive disorders. Our view is that immune responses caused by metabolic stress might play a major role in this conundrum.